KONTEKSTUALISASI PEMAHAMAN HADIS NABI TENTANG RIBA - Mohammad Nawir (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
This study explores the issue of usury from the point of view of the hadith of the prophet. For the sake of finding supporting data against the argument that usury is not justified in Islamic law. This study uses a hadith science approach and various kinds of scientific approaches as supporters to understand the content of the hadith about usury. In this study, the authors found that before this study many criteria and benchmarks for usury were found in relation to buying and selling, exchanging, saving and borrowing, and knowing the laws of usury transactions clearly. Of course, studies on usury have been written by many Islamic law researchers, including Abdul Gofur with the theme of the concept of usury in the Koran, Riya Rohma Setyawati et al with the theme of usury in the view of Islam, Miriam So Phia with the theme of usury in Islamic jurisprudence, Abdurrahim Abdul Hamid al-sa'ati with the theme al-'illah al-Iqtishadiyah li tahrim al-Riba al-Nasiah wa al-Fadhl. Nevertheless, the author has its own uniqueness in examining the issue of usury in terms of the methods and approaches applied in this study. The approaches applied in this research include: First, the author uses a hadith science approach in conducting research, in order to be able to explore and explore the context of the prophet's hadith accurately. Second, the author uses various scientific approaches that can be a sharp tool in realizing an objective research. Abstrak Penelitian ini mendalami persoalan riba dari sudut pandangan hadis nabi. Demi ditemukannya data penguat terhadap argumen riba itu tidak dibenarkan dalam syariat Islam. Kajian ini menggunakan pendekatan ilmu hadis dan erbagai macam pendekatan ilmia sebagai pendukung untuk memahami kandungan hadis tetang riba. Pada penelitian ini penulis menemukan bahwa sebelum penelitian ini telah banyak ditemukan kriteria dan tolak ukur riba dalam kaitannya dengan jual beli, tukar-menukar, simpan pinjam, serta mengetahui hukum transaksi riba secara terang. Tentu saja kajian tentang riba telah banyak ditulis oleh para penelisik hukum Islam di antaranya Abdul Gofur dengan tema Konsep Riba dalam al-Quran, Riya Rohma Setyawati dkk dengan tema Riba dalam pandangan Islam, Miriam So Phia dengan tema Riba In Islamic Jurisprudence, Abdurrahim abdul hamid al-sa’ati dengan tema al-‘illah al-Iqtishadiyah li tahrim al-Riba al-Nasiah wa al-Fadhl. Kendatipun demikian, penulis memiliki keunikan tersendiri dalam mengkaji persoalan riba dari segi metode dan pendekatan yang diterapkan dalam penelitian ini. Pendekatan yang diterapkan dalam penelitian ini di antaranya Pertama, penulis menggunakan pendekatan ilmu hadis dalam melakukan penelitian, agar dapat menelusuri dan mendalami konteks hadis nabi secara akurat. Kedua, penulis menggunakan berbagai pendekatan ilmia yang dapat menjadi alat yang tajam dalam mewujudkan sebuah penelitian yang objektif.